Differential immunological crossreactivity of HeLa keratin antibodies with human epidermal keratins. - Fey, S J (1983)
HeLa cells contain four keratin-like proteins having molecular weights of 50,000 (IEF 31), 48,500 (IEF 36), 44,000 (IEF 44), and 43,500 (IEF 46), respectively. Mouse polyclonal antibodies prepared against two of these keratins (IEF 31 and 46) have been used in this study to identify human epidermal keratins with common antigenic determinants. Using a sensitive immunoprecipitation procedure we show that the IEF 31 antibody crossreacts with three human acidic epidermal keratins, termed K1, K2, and K3, having molecular weights of 44,000, 47,500, and 54,000, respectively. One of these keratins (K1) comigrated with HeLa keratin IEF 44 and exhibited an identical one-dimensional peptide map. This protein is also abundant in basaliomas. In contrast to these results, the IEF 46 antibody showed no crossreactivity with any of the human acidic or basic [35S]methionine-labeled epidermal proteins. The lack of crossreactivity of this antibody was further confirmed by indirect immunofluorescence staining of cryostat sections from human split skin. These results emphasize both the similarity and diversity of antigenic determinants among HeLa and epidermal keratins.